Blend preparation and analysis method based on plasma modification compatibility
The polypropylene insulating material is processed through plasma modification technology and blended with polyolefin elastomer, which solves the problem of poor PP/POE compatibility, significantly improves the electrical-force performance of the cable insulating layer, simplifies the process and reduces costs.
Patent Information
- Application Number
- CN202411619564.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, the compatibility and interface bonding of polypropylene (PP) insulating material and polyolefin elastomer (POE) are poor, resulting in a low modification success rate, complex process and reduced purity of the insulating material, making it difficult to meet the installation requirements of high-voltage cables.
The modified polypropylene insulating material is surface modified by plasma-based modification technology, and the modified polypropylene insulating material is generated by dielectric barrier discharge technology, and then melt blended with the polyolefin elastomer to prepare a modified blend.
It improves the compatibility of polypropylene insulating material and polyolefin elastomer, improves the electrical and force performance of PP/POE blends, solves the problems of low modification success rate and complex process, and has the advantages of small investment, safe, simple operation and strong economical style.
Smart Images

Figure CN119591903A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high voltage and insulation, and in particular to a preparation and analysis method of a blend based on plasma modified compatibility. Background Art
[0002] As the power system gradually develops towards recycling and reuse, polypropylene (PP) has gradually replaced cross-linked polyethylene (XLPE) with its excellent electrical insulation, no need for cross-linking and recyclability, becoming the main research direction of cable insulation materials in the future. However, PP insulation materials have mechanical performance problems such as high rigidity and poor elongation at break, which cannot meet the requirements for the laying and installation of high-voltage cables. In response to this problem, the mainstream modification technology routes for cable PP insulation include grafting modification, nano-modification and blending modification. Among them, the physical modification idea of blending elastomers with PP insulation materials to improve mechanical properties has the advantages of strong economy, simple process flow and obvious performance improvement, and is a more mature physical modification idea in engineering.
[0003] Elastomer ethylene-octene copolymer (Poly Olefin Elastomer, POE), also known as polyolefin elastomer, has become the first choice for PP blending modification due to its low price and excellent electrical and mechanical properties. However, the elastomer POE has the problem of poor compatibility and interface bonding with the polypropylene matrix. At present, there are many reports on the compatibility of modified PP and POE. For example, the modification ideas of using nucleating agents, compatibilizers and grafting to improve the compatibility of PP and POE have made great progress in experiments and mechanisms, but there are problems such as reducing the purity of insulating materials, low modification success rate and complex processes, which make it difficult to put into engineering application.
[0004] Therefore, how to provide a blend preparation and analysis method based on plasma-modified compatibility is a problem that needs to be solved urgently. Summary of the invention
[0005] The embodiment of the present invention provides a method for preparing and analyzing a blend based on plasma modified compatibility, specifically a method for modifying the compatibility of a PP / POE blend, thereby improving the electrical and mechanical properties of the insulation layer of a high-voltage blended polypropylene cable, in order to solve the problems of reducing the purity of the insulating material, low modification success rate, and complex process in the prior art.
[0006] In order to have a basic understanding of some aspects of the disclosed embodiments, a brief summary is given below. This summary is not intended to be a general review, nor is it intended to identify key / important components or to delineate the scope of protection of these embodiments. Its only purpose is to present some concepts in a simple form as a preface to the detailed description that follows.
[0007] According to a first aspect of an embodiment of the present invention, a method for preparing a blend based on plasma-modified compatibility is provided.
[0008] In one embodiment, the method for preparing a blend based on plasma-modified compatibility comprises:
[0009] Based on the plasma processing platform and using dielectric barrier discharge technology, the pre-configured polypropylene insulation material is subjected to plasma surface modification treatment to obtain modified polypropylene insulation material;
[0010] Based on the melt blending technology, the modified polypropylene insulation material and the pre-configured polyolefin elastomer are melt blended to obtain a modified blend.
[0011] In one embodiment, based on a plasma processing platform and using dielectric barrier discharge technology, a pre-configured polypropylene insulation material is subjected to plasma surface modification treatment to obtain a modified polypropylene insulation material comprising:
[0012] The working parameters of the plasma processing platform are set, and the polypropylene insulation material is placed in a modification environment; the polypropylene insulation material is modified by using the dielectric barrier discharge technology in the plasma processing platform, and the obtained modified polypropylene insulation material is stored in a dark place.
[0013] In one embodiment, setting the working parameters of the plasma processing platform and placing the polypropylene insulation material in the modification environment includes:
[0014] The working voltage, working current and flow rate of the plasma processing platform are set; polypropylene insulation material is placed between the quartz glass sheets, and the flow rate of the gas cylinder and the pressure of the reaction chamber are adjusted.
[0015] In one embodiment, based on the melt blending technology, the modified polypropylene insulation material and the pre-configured polyolefin elastomer are melt blended to obtain a modified blend comprising:
[0016] According to the preset ratio of polyolefin elastomer to modified polypropylene insulating material, the modified polypropylene insulating material and the polyolefin elastomer are placed in a constant temperature drying oven for drying;
[0017] Using a torque rheometer, the modified polypropylene insulation material and the polyolefin elastomer are melt-blended to obtain a blend;
[0018] The blend is melted, molded and cooled under preset conditions using a flat vulcanizing machine to obtain a modified blend.
[0019] In one embodiment, the predetermined ratios of the polyolefin elastomer to the modified polypropylene insulation material include 1:9, 2:8 and 3:7.
[0020] According to a second aspect of an embodiment of the present invention, a blend analysis method based on plasma-modified compatibility is provided.
[0021] In one embodiment, the blend analysis method based on plasma modified compatibility comprises:
[0022] Based on the material performance analysis technology, the pre-prepared pre-modified blend and the modified blend were tested respectively, and the physical and chemical properties, electrical properties and mechanical properties of the pre-modified blend and the modified blend were analyzed.
[0023] In one embodiment, based on the material performance analysis technology, the pre-prepared pre-modified blend and the modified blend are tested respectively, and the physical and chemical properties, electrical properties and mechanical properties of the pre-modified blend and the modified blend are analyzed, including:
[0024] The blend before modification and the modified blend were selected respectively; the microstructures of the blend before modification and the modified blend were observed by scanning electron microscopy;
[0025] The crystal morphology of the blends before modification and the modified blends was observed using a polarizing microscope.
[0026] The changes of chemical bonds and functional groups of the pre-modified blends and modified blends were analyzed based on Fourier transform infrared spectroscopy;
[0027] The broadband dielectric spectra of the pre-modified blend and the modified blend are analyzed using a broadband dielectric spectrum tester;
[0028] The breakdown properties of the pre-modified blend and the modified blend were analyzed using a universal breakdown tester.
[0029] The tensile properties of the pre-modified and modified blends were analyzed using a universal tensile testing machine at room temperature.
[0030] In one embodiment, the blend before modification includes a polyolefin elastomer and a polypropylene insulation material;
[0031] Wherein, the content of the polyolefin elastomer in the blend before modification includes 10%, 20% and 30%.
[0032] In one embodiment, the modified blend includes a polyolefin elastomer and a modified polypropylene insulation material;
[0033] Wherein, the content of the polyolefin elastomer in the modified blend includes 10%, 20% and 30%.
[0034] In one embodiment, observing the microscopic morphology of the pre-modified blend and the modified blend using a scanning electron microscope comprises:
[0035] The pre-modified blend and the modified blend are placed in liquid nitrogen for quenching treatment, and gold is sprayed on the cross section after the quenching treatment;
[0036] The microstructures of the interfaces between the pre-modified and modified blends were observed using a scanning electron microscope.
[0037] In one embodiment, observing the crystalline morphology of the pre-modified blend and the modified blend using a polarizing microscope comprises:
[0038] Configure the sample thickness of the blend before modification and the modified blend, and set the magnification of the polarizing microscope.
[0039] In one embodiment, analyzing the changes in chemical bonds and functional groups of the pre-modified blend and the modified blend based on Fourier transform infrared spectroscopy includes: setting a test wave number range of Fourier transform infrared spectroscopy.
[0040] In one embodiment, analyzing the broadband dielectric spectra of the pre-modified blend and the modified blend using a broadband dielectric spectrum tester comprises:
[0041] The sample diameters of the pre-modified blend and the modified blend are configured, and the test temperature and frequency range of the broadband dielectric spectrum tester are set.
[0042] In one embodiment, the breakdown properties of the pre-modified blend and the modified blend are analyzed using a universal breakdown tester, including:
[0043] The breakdown experiments were carried out on the blends before modification and the modified blends using cylindrical electrodes, and the blends before modification and the modified blends were placed in silicone oil, respectively.
[0044] In one embodiment, analyzing the tensile properties of the pre-modified blend and the modified blend at room temperature using a universal tensile testing machine comprises:
[0045] The shapes of the blend before modification and the modified blend are set to be dumbbell-shaped; and the tensile test results of the blend before modification and the modified blend are calculated respectively.
[0046] In one embodiment, respectively calculating the tensile test results of the pre-modified blend and the modified blend includes:
[0047] The unmodified blend and the modified blend were subjected to several tensile tests, respectively, and the average value of the tensile test results was calculated.
[0048] The technical solution provided by the embodiment of the present invention may have the following beneficial effects:
[0049] The present invention uses air plasma to modify polypropylene (PP) insulation material, and then blends it with polyolefin elastomer (POE) to prepare samples, and compares and analyzes the performance of the samples before and after the treatment. The preparation method of the present invention can improve the compatibility of polypropylene insulation material and polyolefin elastomer, thereby improving the electrical properties and mechanical properties of PP / POE blends. The method has the advantages of small investment, safety, simple operation, strong economy and applicable engineering, and is of great significance for improving the mechanical and insulating properties of polypropylene insulation. It provides new ideas for improving the compatibility of polypropylene insulation material and elastomer, and has certain guiding significance for the research and development of cables.
[0050] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.
[0052] Figure 1 is a flow chart of a method for preparing a blend based on plasma-modified compatibility according to an exemplary embodiment;
[0053] Figure 2 is a flow chart of a blend analysis method based on plasma modified compatibility according to an exemplary embodiment;
[0054] Figure 3 is a flow chart of plasma modified PP insulation material according to an exemplary embodiment;
[0055] Figure 4 is a flow chart of preparing a PP / POE blended sample according to an exemplary embodiment;
[0056] Figure 5 is a microscopic morphology and elemental analysis diagram of PP insulation material and PP / POE blend according to an exemplary embodiment;
[0057] Figure 6 is a diagram showing the crystal morphology of PP / POE blends before and after modification according to an exemplary embodiment;
[0058] Figure 7 is an infrared spectrum of PP / POE blends before and after modification according to an exemplary embodiment;
[0059] Figure 8 is a diagram showing relative dielectric constants of PP / POE blends before and after modification according to an exemplary embodiment;
[0060] Fig. 9 is a diagram showing the breakdown characteristics of PP / POE blends before and after modification according to an exemplary embodiment;
[0061] Fig.10 It is a diagram showing the mechanical properties of PP insulation material and PP / POE blends before and after modification according to an exemplary embodiment. DETAILED DESCRIPTION
[0062] The following description and accompanying drawings fully illustrate the specific embodiments of this article so that those skilled in the art can practice them. Parts and features of some embodiments may be included in or replace parts and features of other embodiments. The scope of the embodiments of this article includes the entire scope of the claims, as well as all available equivalents of the claims. Herein, the terms "first", "second", etc. are only used to distinguish one element from another, without requiring or implying any actual relationship or order between these elements. In fact, the first element can also be called the second element, and vice versa. Moreover, the terms "include", "comprise" or any other variant thereof are intended to cover non-exclusive inclusion, so that the structure, device or equipment including a series of elements includes not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such structure, device or equipment. In the absence of more restrictions, the elements defined by the sentence "including one..." do not exclude the existence of other identical elements in the structure, device or equipment including the elements. Each embodiment is described in a progressive manner herein, and each embodiment focuses on the differences from other embodiments, and the same and similar parts between the embodiments can be referred to each other.
[0063] The terms "longitudinal", "lateral", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc. in this document indicate the orientation or position relationship based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing this document and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In the description of this document, unless otherwise specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a mechanical connection or an electrical connection, it can also be the internal communication of two elements, it can be a direct connection, or it can be an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms can be understood according to specific circumstances.
[0064] As used herein, the term "plurality" means two or more than two, unless otherwise specified.
[0065] In this document, the character " / " indicates that the preceding and following objects are in an "or" relationship. For example, A / B means: A or B.
[0066] In this article, the term "and / or" is a description of the association relationship between objects, indicating that three relationships may exist. For example, A and / or B means: A or B, or, A and B.
[0067] It should be understood that, although the various steps in the flow chart are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear description in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a portion of the steps in the figure may include multiple sub-steps or multiple stages, and these sub-steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these sub-steps or stages is not necessarily to be carried out in sequence, but can be executed in turn or alternately with other steps or at least a portion of the sub-steps or stages of other steps.
[0068] Each module in the device or system of the present application can be implemented in whole or in part by software, hardware, or a combination thereof. The above modules can be embedded in or independent of a processor in a computer device in the form of hardware, or can be stored in a memory in a computer device in the form of software, so that the processor can call and execute operations corresponding to the above modules.
[0069] In the absence of conflict, the embodiments of the present invention and the features of the embodiments may be combined with each other.
[0070] Figure 1 An embodiment of the blend preparation method based on plasma-modified compatibilization of the present invention is shown.
[0071] In this optional embodiment, the blend preparation method based on plasma modified compatibility comprises:
[0072] S101, based on a plasma processing platform and using dielectric barrier discharge technology, performing plasma surface modification treatment on a pre-configured polypropylene insulation material to obtain a modified polypropylene insulation material;
[0073] S103, based on melt blending technology, melt blending the modified polypropylene insulation material and the pre-configured polyolefin elastomer to obtain a modified blend.
[0074] Figure 2 An embodiment of the blend analysis method based on plasma-modified compatibility of the present invention is shown.
[0075] In this optional embodiment, the blend analysis method based on plasma-modified compatibility comprises:
[0076] S201. Based on the material performance analysis technology, the pre-prepared pre-modified blend and the modified blend are tested respectively, and the physical and chemical properties, electrical properties and mechanical properties of the pre-modified blend and the modified blend are analyzed.
[0077] In order to facilitate understanding of the above technical solutions of the present invention, the above technical solutions of the present invention are further described below from the perspective of architecture and principle, as follows:
[0078] The present invention is mainly divided into two aspects. On the one hand, a method for modifying PP insulation material using air plasma treatment and a method for preparing a modified PP / POE blend by modifying PP insulation material and POE elastomer, specifically Figure 3-Figure 4 On the other hand, the method of using physical and chemical properties characterization methods (SEM, FTIR, POM) to determine the compatibility of the insulation phase and the elastomer and the method of using (broadband dielectric spectrum, volume resistivity, breakdown field strength, breaking elongation) and other experiments to evaluate the electrical-mechanical properties of cable insulation samples are shown below.
[0079] (1) Plasma modification
[0080] The PP insulation material was modified by using a subatmospheric pressure plasma processing platform (e.g., HPD-2400), with the working voltage set to 220 V, the working current set to 1.9 A, and the flow rate set to 100 mL / min. Figure 3 As shown. The experiment used dielectric barrier discharge technology to perform plasma surface modification on PP materials. First, the PP insulation material was placed between the upper and lower quartz glass sheets. Second, the power was turned on, and the flow of the gas cylinder and the pressure of the reaction chamber were adjusted. Finally, the PP insulation material was bombarded with air plasma for 5 minutes. The modified PP insulation material was stored away from light and left to stand at 70°C for 18 hours.
[0081] Plasma modification can achieve: the electrical energy absorbed by the material surface is used for gas phase chemical reactions, thus breaking through the limitations of traditional chemical methods, achieving unconventional chemical reactions, and improving the surface properties of materials. Plasma technology is very mature: as early as the 1980s, research on plasma in the field of materials gradually became active. In the 1990s, more than 90% of plastic packaging materials in the world required plasma surface treatment and modification. Entering the 21st century, plasma modification technology has a broad application background in the fields of semiconductor materials, polymer films and superconducting materials. In addition, compared with traditional modification methods, plasma modification has the advantages of low investment, simple operation and suitability for engineering applications.
[0082] (2) Preparation of PP / POE blend samples
[0083] The study selected PP insulation material (e.g., T30S) and POE elastomer (e.g., 871L) to prepare PP / POE blended samples. The preparation process is as follows: Figure 4 As shown, the PP insulation material and POE elastomer are placed in a 50°C constant temperature drying oven for drying according to the formula ratio. The PP insulation material and the POE elastomer are melt-blended at 160°C for 30 minutes using a torque rheometer to obtain a PP / POE blend. The PP / POE blend is melted and molded using a flat vulcanizer at 180°C and 10Mpa, and finally cooled to obtain a PP / POE blended sample. The content of elastomer and insulation material is changed respectively, and the above process is repeated to prepare PP / POE blended samples. The sample types are shown in Table 1. m-pp represents plasma-modified PP.
[0084] Table 1 Sample type and component content
[0085] Specimen type Whether modified PP content POE content PP / 10%POE no 90% 10% PP / 20%POE no 80% 20% PP / 30%POE no 70% 30% m-PP / 10%POE yes 90% 10% m-PP / 20%POE yes 80% 20% m-PP / 30%POE yes 70% 30%
[0086] (3) Comparative analysis of sample performance before and after plasma treatment
[0087] The broadband dielectric spectrum test instrument is used to test the broadband dielectric spectrum of the PP / POE blended sample. The sample is a circular sample with a diameter greater than 25 mm, the test temperature is 25°C, and the frequency range is 100-106 Hz.
[0088] The performance analysis of the samples prepared in (2) was carried out. The changes in the physical and chemical properties, electrical properties and mechanical properties of the samples were compared and analyzed by means of scanning electron microscopy, polarizing microscopy, Fourier transform infrared spectroscopy, broadband dielectric spectrum, volume resistivity, breakdown test, etc., and the influence mechanism of plasma treatment on its microstructure, electrical properties and mechanical properties was further discussed.
[0089] The specific analysis includes:
[0090] Three PP / POE blends with different components before and after plasma modification were selected as samples, and were marked as PP / 10% POE; PP / 20% POE; PP / 30% POE; m-PP / 10% POE; m-PP / 20% POE; and m-PP / 30% POE.
[0091] 1) The microstructure of the PP / POE blended sample was observed using a scanning electron microscope (SEM). The sample was placed in liquid nitrogen for quenching treatment, and the cross section was sprayed with gold to observe the microstructure of the interface between PP and POE before and after modification under a scanning electron microscope.
[0092] like Figure 5 As shown in the figure, the surface of the unmodified PP insulation material sample is relatively smooth. The surface of the PP insulation material sample is bombarded by air plasma, and its surface roughness is significantly increased under physical and chemical effects. The interface layer of the PP / POE blend shows a "sea-island" structure before modification. There are obvious differences in the structure and distribution of the two-phase materials, and the interface layer has a clear outline. The structure and distribution of the two-phase materials of the blend after plasma modification are fuzzy, the thickness of the interface layer increases, a small amount of "bridge" appears between the two phases, and the compatibility is significantly enhanced. There is a small amount of O element in the blend before modification. This is because during the melt blending or hot pressing process, the temperature is as high as 180°C, and the sample is partially oxidized. The content of O element increases significantly after modification. This is because when the PP insulation material is treated with air plasma, more oxygen-containing functional groups are grafted on its surface.
[0093] 2) Polarizing Microscope (POM) was used to test the crystal morphology of PP / POE blended samples before and after modification. The sample thickness was 30 μm and the microscope magnification was 500 times.
[0094] like Figure 6 As shown in the figure, the spherulites in the PP / POE blend before plasma modification grew completely, the spherulites had clear outlines, and the crystallization process was highly random. The crystallization products of the modified PP / POE blend were relatively evenly dispersed broken crystals, the crystal size was significantly reduced, and there was no obvious outline. The main reason is that after plasma modification of PP, on the one hand, the crystal structure on the surface of PP was destroyed; on the other hand, during blending, PP and POE were more tightly combined and the binding energy increased, the resistance of PP crystallization process increased, and crystallization needed to break through a large potential barrier, resulting in the inability to form complete spherulites. The POM results indirectly prove that the compatibility of PP and POE has been improved.
[0095] 3) Fourier Transform Infrared Spectrometer (FTIR) was used to analyze the changes in chemical bonds and functional groups of PP / POE blends before and after modification. The test wave number range was 500 cm -1 -4000cm -1 .
[0096] like Figure 7 As shown, 1371cm -1 and 1456cm -1 They are the symmetric stretching vibration peak and asymmetric stretching vibration peak of the CH bond on -CH3, 2917cm -1 It is the asymmetric stretching vibration peak of -CH2. The above characteristic peaks indicate that the measured substance has the characteristics of alkane. Figure 6 Medium 1738cm -1The peak is the stretching vibration peak of C=O, indicating that the substance tested has the characteristics of ester group. In summary, the substance tested has the common characteristics of olefin and ester group.
[0097] The infrared spectrum of m-PP / 30%POE shows that 2850cm -1 and 2950cm -1 The symmetrical stretching vibration peak and asymmetrical stretching vibration peak of -CH2 are shown at 3302cm after modification. The crystal structure is destroyed after modification, so the peak values increase and decrease significantly. -1 A broad absorption band appeared at 3450cm -1 -4000cm -1 There is a small peak fluctuation between the two, which is the free gas phase OH in the carboxyl group. In summary, when air plasma is modified in PP insulation material, the crystal structure of PP surface is destroyed, and oxygen-containing functional groups such as C=O, -OH and C-OOH exist in PP / POE blends.
[0098] 4) Use a broadband dielectric spectrum tester to test the broadband dielectric spectrum of the PP / POE blended sample. The sample is a circular sample with a diameter greater than 25 mm, the test temperature is 25°C, and the frequency range is 100-106 Hz.
[0099] like Figure 8 As shown, the dielectric constants of PP insulation and PP / POE blends show a downward trend with increasing frequency. The dielectric constant of PP insulation is 2.58, which is close to the dielectric constant of each PP / POE blend sample, and the difference is within 0.05. The dielectric constant of the modified PP / POE blend sample changes little. When the frequency is 50Hz, the m-PP / 10%POE and m-PP / 30%POE samples increase by 0.05 and 0.03 respectively compared with the PP / 10%POE and PP / 30%POE samples, and the m-PP / 20%POE sample decreases by 0.03 compared with the PP / 20%POE sample.
[0100] 5) The breakdown performance of the PP / POE blended sample was tested using a universal breakdown tester. A cylindrical electrode was used to perform the breakdown test, and a matrix resin sample with a thickness of 0.3 mm was placed in silicone oil and subjected to 10 breakdown tests.
[0101] like Fig. 9 As shown in the figure, the breakdown field strength of PP insulation material is 47.22 kV / mm, and the breakdown field strength of PP decreases after adding POE to PP. The breakdown strength of PP / POE blends decreases with the increase of the content of elastomer POE.
[0102] The breakdown strength of the modified PP / POE blend samples has been improved to varying degrees compared to that before modification. The more POE content, the more obvious the improvement in breakdown strength. The breakdown strength of the m-PP / 30%POE sample has increased significantly, up 17.7% from the PP / 30%POE sample. According to the free volume breakdown theory, there are more interface layers between the insulating phase and the elastomer phase in the PP / 30%POE sample, and the free volume travel in the blended sample is larger, so the breakdown strength is smaller. After plasma modification, the combination energy between the PP insulating phase and the POE elastomer in the m-PP / 30%POE sample is larger, the thickness of the interface layer increases, and the free volume travel decreases significantly, so the breakdown strength is much improved compared to the PP / 30%POE sample.
[0103] 6) Use a universal tensile testing machine to perform a tensile test on the sample at room temperature. The sample is a dumbbell of 75mm×4mm×2mm. The reference standard number is: ISO 527-3-2018, the tensile rate is 50mm / min, and each sample is tested five times to calculate the average value to obtain the result.
[0104] like Fig.10 As shown, the tensile strength of the PP sample is 28MPa and the elongation at break is 15%. With the increase of the elastomer POE content in the PP / POE blend, the tensile strength of the blend shows a downward trend, and the elongation at break shows an upward trend. The tensile strength of the modified PP / POE blends increased slightly, and the elongation at break increased significantly. The tensile strength of the m-PP / 10% POE sample increased by 9% compared with the PP / 10% POE sample, which is a significant increase; the more POE content, the more obvious the increase in elongation at break, and the m-PP / 30% POE sample increased by 36% compared with the PP / 30% POE sample.
[0105] In PP / POE blends, PP as the matrix phase is the main factor affecting the tensile strength. Although the compatibility between the PP matrix phase and the POE elastomer phase is improved after modification, due to the low content of the elastomer phase, the increased bonding force between the two phases has little effect on the tensile strength of the blend, and the ratio of POE and PP has not changed, so the tensile strength of the modified blend is only slightly improved. The elongation at break of the PP / POE blend is mainly affected by the POE elastomer phase. After modification, the dispersion of the elastomer phase in the matrix phase is improved, the thickness of the interface layer is increased, the bonding between the two phases is tighter, and the toughening effect of the elastomer is more obvious, so the elongation at break of the blend is higher.
[0106] The present invention is not limited to the structures which have been described above and shown in the drawings, and various modifications and changes may be made without departing from the scope thereof. The scope of the present invention is limited only by the appended claims.
Claims
1. A method for preparing a blend based on plasma modified compatibility, characterized in that: include: Based on the plasma processing platform and using dielectric barrier discharge technology, the pre-configured polypropylene insulation material is subjected to plasma surface modification treatment to obtain modified polypropylene insulation material; Based on the melt blending technology, the modified polypropylene insulation material and the pre-configured polyolefin elastomer are melt blended to obtain a modified blend.
2. The method for preparing a blend based on plasma modified compatibility according to claim 1, characterized in that: The plasma treatment platform is used to perform plasma surface modification treatment on the pre-configured polypropylene insulation material using dielectric barrier discharge technology to obtain the modified polypropylene insulation material, which includes: The working parameters of the plasma processing platform are set, and the polypropylene insulation material is placed in a modification environment; the polypropylene insulation material is modified by using the dielectric barrier discharge technology in the plasma processing platform, and the obtained modified polypropylene insulation material is stored in a light-proof manner.
3. The method for preparing a blend based on plasma modified compatibility according to claim 2, characterized in that: The step of setting the working parameters of the plasma treatment platform and placing the polypropylene insulation material in the modification environment includes: The working voltage, working current and flow rate of the plasma processing platform are set; polypropylene insulation material is placed between the quartz glass sheets, and the flow rate of the gas cylinder and the pressure of the reaction chamber are adjusted.
4. The method for preparing a blend based on plasma modified compatibility according to claim 1, characterized in that: The modified polypropylene insulation material and the pre-configured polyolefin elastomer are melt-blended based on the melt-blending technology to obtain the modified blend, which comprises: According to the preset ratio of polyolefin elastomer to modified polypropylene insulating material, the modified polypropylene insulating material and the polyolefin elastomer are placed in a constant temperature drying oven for drying; Using a torque rheometer, the modified polypropylene insulation material and the polyolefin elastomer are melt-blended to obtain a blend; The blend is melted, molded and cooled under preset conditions using a flat vulcanizing machine to obtain a modified blend.
5. The method for preparing a blend based on plasma modified compatibility according to claim 4, characterized in that: The preset ratios of the polyolefin elastomer to the modified polypropylene insulating material include 1:9, 2:8 and 3:
7.
6. A blend analysis method based on plasma modified compatibility, characterized in that: include: Based on the material performance analysis technology, the pre-prepared pre-modified blend and the modified blend were tested respectively, and the physical and chemical properties, electrical properties and mechanical properties of the pre-modified blend and the modified blend were analyzed.
7. A blend analysis method based on plasma modified compatibility according to claim 6, characterized in that: The material performance analysis technology is based on testing the pre-modified blend and the modified blend respectively, and analyzing the physical and chemical properties, electrical properties and mechanical properties of the pre-modified blend and the modified blend, including: The blend before modification and the modified blend were selected respectively; the microstructures of the blend before modification and the modified blend were observed by scanning electron microscopy; The crystal morphology of the blends before modification and the modified blends was observed using a polarizing microscope. The changes of chemical bonds and functional groups of the pre-modified blends and modified blends were analyzed based on Fourier transform infrared spectroscopy; The broadband dielectric spectra of the pre-modified blend and the modified blend are analyzed using a broadband dielectric spectrum tester; The breakdown properties of the pre-modified blend and the modified blend were analyzed using a universal breakdown tester. The tensile properties of the pre-modified and modified blends were analyzed using a universal tensile testing machine at room temperature.
8. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The blend before modification includes polyolefin elastomer and polypropylene insulating material; Wherein, the content of the polyolefin elastomer in the blend before modification includes 10%, 20% and 30%.
9. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The modified blend comprises a polyolefin elastomer and a modified polypropylene insulating material; Wherein, the content of the polyolefin elastomer in the modified blend includes 10%, 20% and 30%.
10. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of observing the microscopic morphology of the pre-modified blend and the modified blend using a scanning electron microscope comprises: The pre-modified blend and the modified blend are placed in liquid nitrogen for quenching treatment, and gold is sprayed on the cross section after the quenching treatment; The microstructures of the interfaces between the pre-modified and modified blends were observed using a scanning electron microscope.
11. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of observing the crystalline morphology of the pre-modified blend and the modified blend using a polarizing microscope comprises: Configure the sample thickness of the blend before modification and the modified blend, and set the magnification of the polarizing microscope.
12. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of analyzing the changes of chemical bonds and functional groups of the pre-modified blend and the modified blend based on Fourier transform infrared spectroscopy includes: setting a test wave number range of the Fourier transform infrared spectroscopy.
13. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of analyzing the broadband dielectric spectra of the pre-modified blend and the modified blend using a broadband dielectric spectrum tester comprises: The sample diameters of the pre-modified blend and the modified blend are configured, and the test temperature and frequency range of the broadband dielectric spectrum tester are set.
14. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of analyzing the breakdown properties of the pre-modified blend and the modified blend using a universal breakdown tester includes: The breakdown experiments were carried out on the blends before modification and the modified blends using cylindrical electrodes, and the blends before modification and the modified blends were placed in silicone oil, respectively.
15. The blend analysis method based on plasma modified compatibility according to claim 7, characterized in that: The method of analyzing the tensile properties of the pre-modified blend and the modified blend at room temperature using a universal tensile testing machine includes: The shapes of the blend before modification and the modified blend are set to be dumbbell-shaped; and the tensile test results of the blend before modification and the modified blend are calculated respectively.
16. The blend analysis method based on plasma modified compatibility according to claim 15, characterized in that: The tensile test results of the blend before modification and the modified blend are calculated separately, including: The unmodified blend and the modified blend were subjected to several tensile tests, respectively, and the average value of the tensile test results was calculated.